" التداولية: نظرية افعال الكلام عند جون أوستين وجون سيرل وبول غرايس" (Comprehensive Journal of Science, 2025)
This study aims to reveal the linguistic shift that moved language from a closed structure to open communication and usage within context, by examining the philosophical roots of the communicative approach in the philosophy of language and revealing the communicative foundations established by pioneers such as John Austin, to its development by John Searle and Paul Grice, who expanded the concept of pragmatics to include the psychological and social dimensions of meaning through their theory of cooperation and implicatures. The study relied on the descriptive-analytical approach, which seems most appropriate for the nature of the subject, describing the views of pragmatist philosophers, then analyzing them and revealing the agreements and differences between them and how pragmatism developed through them. The study reached several conclusions: 1- A speech act is an act that we perform simply by uttering words. 2- Pragmatics is concerned with the speaker's intentions and the implied meaning of speech. 3- The principle of cooperation represents a social communicative context among speakers. The study also recommends focusing on the study of meaning and intention as a fundamental concept related to the concepts of the philosophy of language.Translated with DeepL.com (free version).